Review of literature on methods and processes to produce bioethanol from banana peels for disinfection and sanitation of the environment in communities, central region of Mozambique (Research, Society and Development, 2024)
The demand for alcohol for human health and as an energy resource has attracted the attention of many researchers who have identified accessible and sustainable raw materials for bioethanol production at low cost and with reduced environmental impact. Among the variety of raw material for bioethanol, most come from agricultural and livestock products, in this case banana peel. The feedstock should not disequilibria food safety and should be sourced with adequate efficiency without involving too many complex procedures. Thus, the present research, through a literature review, seeks to discuss efficient methods and procedures to produce bioethanol from banana peels as agricultural waste, for application as a disinfectant of products, in human health and as energy source for households, in the context of rural areas. Many studies point to banana peels as an alternative feedstock for bioethanol production, however communities in Mozambique despite having this resource in abundance, still do not explore systematically in maximum efficiency due to the culture issues and anthropogenic knowledge. The results to maximize the efficiency are among control of production parameters, alkaline pretreatment with Sodium Hydroxide (NaOH), saccharification in a plastic reservoir with less than 10% of Sulfuric Acid (H2SO4) for hydrolysis, enzymatic fermentation using Saccharomyces cerevisiae, distillation at controlled temperatures from 80 up to 120 0C.